Structure and superconductivity of protactinium hydrides under high pressure. (23rd May 2019) - Xiao, Xuehui; Duan, Defang; Xie, Hui; Shao, Ziji; Li, Da; Tian, Fubo; Song, Hao; Yu, Hongyu; Bao, Kuo; Cui, Tian
Abstract: We systematically study the stability, crystal structure, electronic property, and superconductivity of protactinium hydride (PaH n ) ( n = 1–9) at a pressure range of 1 atm to 300 GPa by using the first principle of density functional theory. PaH n compounds are very rich, featuring six stoichiometries, such as PaH, PaH3, PaH4, PaH5, PaH8 and PaH9 . PaH8 possesses the highly symmetrical crystal structure Fm -3 m with cubic H8 units, which is predicted to be thermodynamically stable above 32 GPa. This phase maintains a dynamically stable decompression at 10 GPa. Electron–phonon coupling (EPC) calculations show that Fm -3 m -PaH8 exhibits high superconducting critical transition temperature ( T c ) value of 79 K at 10 GPa due to a strong EPC and large logarithmic average frequency. The T c values of Fm -3 m -PaH8 decrease with increasing pressure. Interestingly, superconducting PaH8 appears at low pressure, prompting experimental research.